MENGEMBANGKAN PENDIDIKAN KEWIRAUSAHAAN DALAM MATA KULIAH MANAJEMEN PEMASARAN DENGAN MENGGUNAKN PROJECT BASED LEARNING : STIJDI KASUS I.JNIVERSITAS CIPUTRA - Wiarawan ED Radianto (Fakultas Bisnis UKDW, 2009)
The need of entrepreneurial skill is emergtng along with the increasing of unemployment. Consequently, many higher education especially university integrate entrepreneurship in the carricalum. But yet, there are many universities still looking for the appropriate model to implement entrepreneurial skill.The essence of entrepreneuriql education is developing the spirit af entrepreneur of students in order to become entrepreneur instead of employee. Therefore, there are marcy methodologies can be studied further in term of integrating entrepreneurial tocurriculum.This study used Project Based Learning method (PBL). This method employed in Marketing Management course. The purpose of the study is to develop the spirit of entrepreneurship especially creativity and innovative, opportunity creation, and calculated risk taking. The result shows that PBL is very effectiue to increase sofi skill and to develop creativity and innovative. Also the student can understand easily aboutthe concepts of marketing.Keywords: Project Based Learning, student, entreprensurship, marketing management.